The Location of the Antimicrobial Peptide Maculatin 1.1 in Model Bacterial Membranes - Le Brun, Anton P.; Zhu, Shiying; Sani, Marc-Antoine; Separovic, Frances (Frontiers in Chemistry, 2020)
Maculatin 1.1 (Mac1) is an antimicrobial peptide (AMP) from the skin secretions of Australian tree frogs. In this work, the interaction of Mac1 with anionic phospholipid bilayers was investigated by NMR, circular dichroism (CD) spectroscopy, neutron reflectometry and molecular dynamics (MD). In buffer, the peptide is unstructured but in the presence of anionic (DPC/LMPG) micelles or (DMPC/DMPG/DHPC) bicelles adopts a helical structure. Addition of the soluble paramagnetic agent gadolinium (Gd-DTPA) into the Mac1-DPC/LMPG micelle solution showed that the N-terminus is more exposed to the hydrophilic Gd-DTPA than the C-terminus in micelles. 2H and 31P solid-state NMR showed that Mac1 had a greater effect on the anionic lipid (DMPG). A deuterium labelled Mac1 used in neutron reflectometry experiments indicated that the AMP spanned across anionic (PC/PG) bilayers, which was compatible with MD simulations. The simulations also showed that Mac1 orientation remained transmembrane in bilayers and on the surface of the micelles regardless of the lipid charge. Thus, the peptide orientation appears to be more susceptible to curvature than the effect of the charged surface. These results support the formation of transmembrane pores by Mac1 in model bacterial membranes.